The first record of subtropical insects (Thysanoptera) in central Europe: long‐distance transport of airborne thrips, applying three‐dimensional backward trajectories. (12th October 2017) - Makra, László; Bodnár, Károly; Fülöp, Andrea; Orosz, Szilvia; Szénási, Ágnes; Csépe, Zoltán; Jenser, Gábor; Tusnády, Gábor; Magyar, Donát
Abstract: The present study reports the first occurrence and flight period of three species, namely Scolothrips tenuipennis zur Strassen 1965, Frankliniella schultzei Trybom, 1910 and Zurstrassenia figuratus zur Strassen, 1968 (Thysanoptera: Thripidae), in Hungary. A fourth, undescribed species belonging to the genus Caliothrips was also captured. The distribution area of these species is North Africa and it is hypothesized that they are transported to Hungary via long‐distance air currents. Data for a suction trap are examined in South–East Hungary, in the 3‐year period 2002–2004 from May to September. A three‐dimensional back‐trajectory analysis based on the Hybrid Single‐Particle Lagrangian Integrated Trajectory (HYSPLIT) transport and dispersion model was performed for the observation days to determine the origin and path of air masses and evaluate of the possibility of long‐distance transport of thrips species. Surprisingly, the analysis showed that only a few percent of the back trajectories originated or passed over North Africa. The results suggest that the captured thrips species could survive long‐distance transport at low‐level trajectories and establish new populations in Western Europe, the eastern part of Europe and Northern Central Europe, which together serve as source areas for the long‐range transport of thrips to the target station.